Analysis of Digital Governance Framework Implementation to Enhance Digital Transformation - Farhana Zahra (RAM PUBLISHER, 2025)
Digital transformation (DT) is increasingly crucial for public and private organizations seeking agility and efficiency. However, many entities pursue DT initiatives without first establishing a structured digital governance framework, resulting in fragmented implementation and strategic misalignment. This study aims to analyze how the absence of governance mechanisms affects transformation effectiveness and identify foundational elements necessary to initiate governance in such contexts. The novelty of this research lies in its analytical focus on organizations lacking pre-existing governance structures. Unlike prior studies that assume the presence of governance, this research offers insights for institutions starting from zero. Using a qualitative descriptive method through literature review and document analysis, this study investigates key governance gaps, risks, and challenges in low-governance environments. The findings reveal that the absence of digital governance leads to inefficiencies, redundant systems, poor risk management, and low accountability. By synthesizing best practices and proposing phased implementation strategies, the research provides practical guidance to build governance capabilities from the ground up. This study offers both theoretical contributions and actionable recommendations for sustainable digital transformation.